Improving Pregnancy Preparedness: Impact of Preconception Education on Folic Acid Awareness in Women of Childbearing Age - Hidayati, Tutik; Iis Hanifah; Yuliana, Wahida (Jurnal Kebidanan Midwiferia, 2026)
Background: Preconception is an important early stage before pregnancy to determine the quality of the baby to be born. Approximately 24–60% of women, both in developing and developed countries, experience folic acid deficiency because the folic acid content in their daily diet is insufficient to meet the needs of pregnant women. Objectives: The purpose of this study was to analyze the effect of education about the importance of folic acid on healthy pregnancy preparation in women of childbearing age in Condong Village. Method: This study design was preeksperimen. The research variables were measured at a certain time to obtain a picture of the situation at that time. The population in this study were all women of childbearing age, totaling 67 people. The sampling technique used simple random sampling, resulting in a sample of 46 people. Data collection used a questionnaire, and analyzed using the Wilcoxon statistical test. The results of the study showed that preparation in planning a healthy pregnancy before being given education was sufficient for 26 respondents (56.5%), and preparation in planning a healthy pregnancy after being given education was good for 27 respondents (58.7%). The Wilcoxon test analysis showed a p-value of 0.000 < 0.005, indicating an effect of preconception education on the role of folic acid on healthy pregnancy planning among women of childbearing age.. Conclusion: This study concludes that there is an effect of preconception education on the role of folic acid on healthy pregnancy planning among women of childbearing age in Condong Village.